Public pedagogy and representations of higher education in popular film: New ground for the scholarship of teaching and learning - Johnstone, Katelyn; Marquis, Elizabeth; Puri, Varun (Teaching and Learning Inquiry, 2018)
Constructions of teaching, learning, and the university within popular culture can exert an important influence on public understandings of higher education, including those held by faculty and students. As such, they constitute a rich site of inquiry for the scholarship of teaching and learning. Drawing on the notion of film as ‘public pedagogy,’ this article analyses representations of higher education within 11 top grossing and/or critically acclaimed films released in 2014. We identify three broad themes across these texts—the purpose of higher education, relationships between students and professors, and the creation of academic identities—and consider the implications and functions of these representational patterns for teaching, learning, and SoTL. Particular attention is given to the difference between the framing of science and arts and humanities disciplines, and to how this might resonate with the contemporary ‘crisis of the humanities.’